Frequência de eqüídeos positivos para anemia infecciosa eqüina no Acre, 1986 a 1996 - Rejane Maria Lemos Santos (2000)
Data from 9.963 formularies of equines from Acre state (1986 - 1996) submited to Equine Infectious Anaemia (EIA) for the AGID test were analyzed. The socio-ecological areas in the Bacia do Alto do Jurua, Alto Acre and Alta Bacia do Purus rivers showed the highest levels of disease frequency characterizing an strong association between these areas and the positiveness. These risk zones are frontiers areas with the state of Amazonas and also with Peru and Bolivia far from the capital of the state of Acre (Rio Branco) where the access by roads is often difficult. The regions Oriental and Rio Branco showed low levels of positiveness. No significant differences were found between animals in regard of species, sex, race and age.